The complexity of environmental policy implementation in China: a set-theoretic approach to environmental monitoring policy dynamics - Jiang, Tianfeng; Gao, Hao; Chen, Gang; Dai, Xiaofei; Xu, Wenjie; Wang, Zerui (Frontiers in Environmental Science, 2024)
The QCA approach, which treats the object of study (dependent variable) as a grouping of conditions, helps to analyse causal complexity issues such as multi-causal concurrency, causal asymmetry, and equivalence, and is suitable for exploring the complex relationship of necessity and sufficiency between multi-conditional combinatorial configurations and the implementation of environmental policies in the policy research framework of this paper. Based on this, this study looks at three dimensions of Sabatier's policy environment framework: the tractability of the problem, the ability of the statute to structure implementation, and non-statutory variables. Starting from the three dimensions of Sabatier's policy environment framework, this study explores in detail the complex configuration of technology availability, change required, financial resources, implementing officials, public support, and socio-economic conditions. The causal relationship between the complex configuration of the six antecedent variables and the implementation of environmental policy is explored in detail. The results based on data from 30 provinces in China identify four different combinations of conditions that match " Opinions on Deepening the Reform of Environmental Monitoring and Improving the Quality of Environmental Monitoring Data " environmental monitoring policy implementation: "priority governance" means that the change required is the most important variable in high-pollution provinces; "money talks" suggests that financial resources are a more important condition in north-western provinces; " coordinated implementation " is associated with non-statutory variables such as public support and socio-economic conditions being neither sufficient nor necessary conditions; and when both the ability of the statute and non-statutory variables were identified as necessary conditions, as in the capital city, this is termed the "comprehensive strategy".The complexity of environmental policy implementation in China: a set-theoretic approach to environmental monitoring policy policy dynamics